Juvenile dermatomyositis in a 6-year-old girl: A case report - Arakkal, Anjali; Peter, Preethy; Cherian, Varghese; Joy, Rojo (Indian Journal of Case Reports, 2024)
Juvenile dermatomyositis (JDM) is the most common inflammatory myositis in children, distinguished by proximal muscle weakness and a characteristic rash. This 6-year-old child presented to the dermatology clinic with a heliotropic rash and later on weakness worsened making her non-ambulant. Genetically pre-disposed children with susceptibility to JDM have upregulation of gene products controlled by type I interferon. Hence, the etiology of JDM is multifactorial, such as genetics and environmental triggers. The diagnostic criteria comprise of heliotropic rash, symmetrical proximal muscle weakness, elevated biomarkers, electromyography, and histopathological changes in muscle. The child was started on intravenous immunoglobulin and immediate clinical remission was attained which emphasized the role of early aggressive institution of therapy in JDM.